A Pedagogical Critique of Learning Practices That Ignore Diagnostic Assessment Results for Student Learning Types - Firdaus, Firdaus; Syahruddin, Syahruddin; Nawir, Nukhrawi; Latang, Latang (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This literature review critically examines teaching practices that ignore diagnostic assessment results for student learning types. The study analyzed 20 research articles to identify the current state of diagnostic assessment implementation in differentiated learning, the pedagogical impacts of neglecting diagnostic assessment results, and conceptual recommendations for optimizing the integration of assessment results in differentiated instruction. The findings reveal varying stages of teachers’ conceptual understanding and implementation skills, with a significant gap between theoretical knowledge and practical application. Neglecting diagnostic assessment results negatively impacts learning effectiveness, motivation, and student achievement. Diagnostic assessment serves as the foundation for differentiated learning by mapping students’ learning readiness, interests, and learning style profiles. The study recommends developing adaptive learning media that systematically integrate diagnostic assessment results into differentiated instructional strategies. This innovative approach has the potential to enhance the effectiveness, efficiency, and equity of learning while supporting the vision of student-centered education in the Merdeka Belajar (Freedom to Learn) curriculum. The study contributes to the theoretical understanding of the relationship between diagnostic assessment and differentiated instruction and offers practical directions for future educational practices oriented towards individual learners’ needs.